Hubungan Sarapan Pagi Dan Jenis Kelamin Dengan Konsentrasi Belajar Pada Siswa SMK Raflesia Depok Tahun 2023 - Agatha, Anggit Fadhila; Linda, Ony (LPPM Sekolah Tinggi Ilmu Kesehatan Pekanbaru Medical Center, 2023)
Concentration is a person's ability to concentrate attention to one particular thing or object, fora relatively long and very long time necessary in the learning process. The aim of this research is to find out The Relationship between Breakfast and Gender Characteristics with Concentration Study. Research with a Cross Sectional design involved 137 students taken by simple random sampling. Concentration was measured using a Stroop test. The measurement of the independent variable is gender characteristics and breakfast consumption habits, the measurement of the dependent variable is Study Concentration. Analysis data using Chi square with statistical software. Univariate results show amounting to 57.7% of students who have poor concentration, students who do not 55.5% of students have breakfast, 50.4% of students are of the same gender Woman. The bivariate test results show that there is a relationship between the characteristics gender (Pvalue = 0.000), breakfast consumption (Pvalue = 0.000) with concentration on learning for students at Raflesia Vocational School, Depok.